KOMUNIKASI KRISIS DALAM NEW NORMAL - Irene Silviani; Inggrit Febriani Pardede; David Cardona Sembiring (Lembaga Penenlitian dan Pengabdian kepada Masyarakat Universitas Darma Agung, 2020)
The Covid-19 pandemic hit the world, and Indonesia was included. Indonesia fought against Covid-19 by modifying the lockdown policy to become a large-scale social limitation (PSBB) that was local in accordance with the severity of the province, district or city. During this pandemic, the world economy and Indonesia experienced a slowdown. The government and strategic study institutions predict that Indonesia will grow low or even negative in 2020. For this reason, the Government is trying to schedule a New Normal policy so that the economic impact of the pandemic does not result in a prolonged crisis. This policy is related to development planning where the Government has set programs, targets and major projects in the National Medium-Term Development Plan (RPJMN) 2020-2024. The government needs to review the medium-term plan considering that in 2020 all programs will shift their focus to handling Covid-19. The government has 3 alternatives in medium-term planning, whether it sticks with the original plan, makes moderate revisions, or replaces it with a new plan by basing the updated assumptions with the coming of the Covid-19 pandemic and the accompanying economic impact.